Experimental study of impurity effects on convective mixing in Hele-Shaw cell with application to CO2 geological sequestration. (February 2023) - Li, Didi; Zhong, Yuhui; Jiang, Xi
Highlights: Effects of common impurities on convective dissolution of CO2 are experimentally investigated. Both single and multiple non-CO2 species (N2, O2 and/or Ar) generally delay the onset of the convective mixing. The co-injection of N2 and/or O2 would weaken the fingering. The growth of the convective fingers with Ar impurity exhibits non-monotonic behavior. The dissolved CO2 inventory of different impure CO2 streams might be similar on the whole in the long term. Abstract: Density-driven convective mixing, i.e ., convective fingering, has been identified to enhance CO2 dissolution trapping in deep saline aquifers. In this study, a series of experiments in Hele-Shaw cells were conducted, and the effects of common impurities (N2, O2, and/or Ar) on the occurrence and development of the convective mixing process were compared and analyzed. It is demonstrated that the existence of these impurities, whether single or their mixture, delayed the onset of convection. However, the subsequent fingering development, including the mixing length and fingering footprint, exhibited different patterns and trends depending on the species and compositions of the impurities. The development and growth of the convective fingers displayed non-monotonic characteristics as a function of the concentration of single impurity Ar. Furthermore, the multiple impurities containing Ar had the potential to enhance the fingering development, especially during the advanced stage. Other than these cases involving Ar, the inclusion of other impurities (N2, and/or O2 ) was found to weaken the fingering development compared with the pure CO2 case. Nevertheless, the results of dissolved CO2 inventory suggested that the effects of different impurities at the same content, both single and multiple, might be similar to each other in the long term, except for the three-impurity case involving Ar. The laboratory experiments in the present study can help establishing a better understanding of the effects of multiple impurities in the application of impure CO2 geological sequestration.